Pengaruh Profitabilitas, Likuiditas, Free Cash Flow dan Ukuran Perusahaan terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2022 - Syarif, Ayunda Mita; Djunaedi, Mira Kartika Dewi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The population of this study consisted of manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2020 period, this study used a purposive sampling and based on the criteria obtained as many as 42 companies with a total of 168 data analysis units. The data used in this study uses secondary data from the company's financial statements. The data analysis method this study uses firm effect and time effect method, and hypothesis testing using Stata data management software version 17. The results showed that profitability showed positive butinsignificant, while liquidity , free cash flow, and company size together show a negative and insignificant effect on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period.